Microstructure and Mechanical Properties of Nb-API X70 Low Carbon Steel - Conde, F. F.; Pina, F. J.; Giarola, J. M.; Pereira, G. S.; Francisco, J. C.; Avila, J. A. [UNESP]; Bose Filho, W. W. (Springer Nature, 2021)
The oil and gas production has grown steadily, and the care with its transportation grid needs to be maintained and expanded. The pipeline used in the transport of gas and oil by-product requires materials with high mechanical strength, toughness, and fatigue resistance. The chemical composition and distribution, amount, and morphology of the final microconstituents of the steel are of paramount importance once it will directly influence the mechanical properties. The fracture toughness is one of the most important mechanical properties for the suitability of the steel for pipeline usage, and is most of the literature with pipelines study does not present tests such as crack tip opening displacement (CTOD), with a steady and controlled crack growth behavior, to evaluate its fracture toughness. This study compares the fracture toughness of the API 5L X70 steel between two plates of steel with different Nb content, 0.06 and 0.09 Nb wt.% by CTOD tests. The mechanical response was correlated to the grain size and distribution. The CTOD parameter was used to assess the fracture toughness at 25 °C and − 60 °C. The microstructures and microconstituents of the two plates of steel were similar. The matrices were composed of ferrite, with bands of secondary products, including degenerated pearlite. Results showed a prone to the formation of a bimodal microstructure, coarse and fine grains, due to the addition of Nb. High-Nb steel presented better fracture toughness than normal-Nb steel at low-temperature.
Keywords: API X70 steel; Fracture toughness; Low-carbon Nb steel; Mechanical properties